FAKTOR-FAKTOR YANG MEMPENGARUHI NASABAH DALAM MENGAMBIL KREDIT (Studi Kasus Bank BAPAS 69 Mertoyudan Magelang) - Luk, Luk (Universitas Muhammadiyah Magelang, 2007)
The more thought competition see bank is business to get and attractive customer or debitur. Problem only bound examine factorservice area, and interest with affect customer take in credit of bank. This sample employed this examine to number 50 . Which people expect can population proxy. Examine hypothesis on this performance with employee Analysis Regression examine witch other statistic with t test, F tst and R Square. Based result analysis witch perform, consolation obttain that influence way above basedd on analysis witch already performance. Parsial way, all variable independent own effect to words bound variable. Result this cary by floor significance posses grade P value most significant.